2005
DOI: 10.1002/pd.1267
|View full text |Cite
|
Sign up to set email alerts
|

First‐trimester diagnosis of conjoined twins

Abstract: Conjoined twins are a rare and complex complication of monozygotic twinning, which is associated with high perinatal mortality. Early prenatal diagnosis of conjoined twins allows better counselling of the parents regarding the management options, including continuation of pregnancy with post-natal surgery, termination of pregnancy or selective fetocide in case of a triplet pregnancy. With the introduction of high-resolution and transvaginal ultrasound imaging, accurate prenatal diagnosis of conjoined twins is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
67
0
5

Year Published

2007
2007
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 97 publications
(72 citation statements)
references
References 34 publications
0
67
0
5
Order By: Relevance
“…Parents need detailed counseling in order to decide among various management options, which include the following: (a) pregnancy continuation and scheduled neonatal surgery, (b) termination of pregnancy, and (c) multifetal pregnancy reduction or selective fetocide in cases of high-order multifetal pregnancies with a component of conjoined fetuses. 31 Diagnosis of conjoined fetuses should be suspected whenever a monochorionic-monoamniotic pregnancy is detected. Sonographic identification of distinct placentae or intervening amniotic membrane(s) rules out fetal conjunction.…”
Section: Prenatal Diagnosismentioning
confidence: 99%
“…Parents need detailed counseling in order to decide among various management options, which include the following: (a) pregnancy continuation and scheduled neonatal surgery, (b) termination of pregnancy, and (c) multifetal pregnancy reduction or selective fetocide in cases of high-order multifetal pregnancies with a component of conjoined fetuses. 31 Diagnosis of conjoined fetuses should be suspected whenever a monochorionic-monoamniotic pregnancy is detected. Sonographic identification of distinct placentae or intervening amniotic membrane(s) rules out fetal conjunction.…”
Section: Prenatal Diagnosismentioning
confidence: 99%
“…The false positive ratio is very high before the 10 th week of pregnancy. In the earlier weeks of pregnancy fetal movements are limited and monochorionic twins may be mistaken for conjoined twins (4). Hence the ultrasonography screening should be repeated in the 11 th and 12 th weeks of pregnancy.…”
Section: Case Reportmentioning
confidence: 99%
“…This patient followed up one week later, and we found that the conjoined twins' one heart had no cardiac activity under the ul- earlier in gestation and monoamniotic twins may be mistaken for conjoined twins. 7 Although the diagnosis of conjoined twins can be made at mid-pregnancy using 2D sonography, diagnosis using 3D sonography has become more prevalent. 8 Pajkrt and Jauniaux 7 concluded that 3D ultrasonography does not provide more accurate information than 2D sonography, and an early diagnosis of conjoined twins is also possible with 2D sonography, as Taner et al 9 recently reported a case of conjoined twins at about seven weeks of gestation.…”
Section: Case Reportmentioning
confidence: 99%